KAJIAN SIKAP RAKYAT MALAYSIA TERHADAP KESETIAAN KEPADA NEGARA - Syed Hussain, Tuan Pah Rokiah; Abd. Muttalib, Ismail (Journal of Techno-Social, 2016)
Allegiance among Malaysians is a matter that should be given priority to ensure national security. The objective of this study is to examine the attitude of Malaysians on their allegiance to the nation based on predetermined areas. This nationwide study involved a total of six zones with 1500 samples taken among Malaysians and was categorised by race. Cross-tabulation analysis was applied on data from questionnaire for reasons of convienience. The results showed that all zones or states were in good condition except for the central zone, represented by the states of Perak, Kuala Lumpur and Selangor which recorded a moderate value of allegiance to the nation. Hence, this study suggests that the current existing programs that can spark allegiance and patriotism to the country should be continued.